ANALISA DAN SIMULASI GAYA POTONG PADA PROSES MACHINE DRILLING DENGAN MENGGUNAKAN SOFTWARE ANSYS - Rahman, Muhammad Iska; Shofa, Ahmad Nur; Setiawan, Listy Fazria (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Drilling process is a cutting metal process with multiple point cutting are used to make cylindrical holes. The process parameters used in drilling process are cutting speed, feed rate and depth of cut. Taguchi-GRA was used for optimizing process parameters. Process parameters and point angle set up exactly so they can reduce cutting force, moment and flank wear. Experiment have done on the drilling process using with S50C steel. Simulation was carried out by ANSYS Software.The results show the distribution of stress in drilling tool. Â Keywords: ANSYS, GRA, Taguchi